REVITALIZATION OF TOURISM AWARENESS GROUPS (POKDARWIS) BASED ON DIGITAL COMMUNICATION TECHNOLOGY TO DEVELOP TOURISM VILLAGES IN MADURA - Wispandono Moch; Faidal Faidal; Imamah Nurul; Yulistiyono Herry (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Villages in Indonesia, especially in Madura, have the potential to be developed into tourist villages that can become tourist destinations for tourists. For this reason, the role of tourism awareness groups (Pokdarwis) is very important because they are the spearhead that connects villages with potential tourists. Pokdarwis must be able to carry out their functions properly so that revitalization becomes a necessity. Of course, the revitalization that is adapted to the current environmental changes is the use of digitalization in every activity, including communication. Therefore, this study aims to: 1) describe the ability of Pokdarwis in utilizing digital communication technology and 2) describe the profile of Pokdarwis in terms of the various elements that support their performance. By using qualitative descriptive research and data analysis using the Miles and Hubberman model, the results of the study indicate that the ability to utilize Pokdarwis digital communication technology as measured by five aspects of ability that reflects digital literacy is still not optimal. Revitalization by providing training or counseling such as digital branding training makes it possible to realize the development of a superior and resilient tourist village Keywords: Revitalization, Pokdarwis, Tourism Village, Digital Communication Technology